ELEMEN QABD (PINDAHAN MILIKAN) DALAM HIBAH: ANALISIS TERHADAP KEPERLUAN DAN PELAKSANAANNYA MENGIKUT PERSPEKTIF UNDANG-UNDANG ISLAM - Nor Muhamad, Nasrul Hisyam (Jurnal Syariah, 2009)
This article generally tries to analyze the position of the qabd (transfer of possession) in the hibah (gift inter vivos) principle according to Islamic Law perspective. The article will be focussing on the opinion of the Muslim scholars in the various schools about the qabd as well as the reported cases in Malaysia. The writer in his article also highlights the purposes of the Sharia (maqasid al-shari‘ah) from the qabd’s requirement in hibah. From the discussion of its condition of validity, it can be concluded that the qabd which is empasized by the majorities scholars is flexible in its application.